'Children's participation is...': Using metaphors to explore lived meanings - Chiara Carla Montà (Pensa MultiMedia, 2023)
Hermeneutic phenomenology provides a framework to understand shared, interrelated, and embodied human existence since it is concerned with meaning-making and revealing what the experience is like. Metaphors, part of poetic language, offer an effective method for presenting complex, rich understandings, giving room for play and ambiguity, and uncovering novel and unexpected ways of conceptualizing experiences. Drawing on a broader case study on the collaboration between the Children's Parliament Scotland and an Aberdeen primary school, this article presents how metaphor was used to gather material on the "meanings of children's participation in decision-making processes". This choice was guided by the epistemological conviction that image-related representations can be significant sources of knowledge about the human world, revealing new meanings that can illuminate both theory and practice.